2019
DOI: 10.13057/biodiv/d200841
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-anatomical structure and DNA barcode of Sonchus arvensis L.

Abstract: Abstract. Wahyuni DK, Rahayu S, Purnama PR, Saputro TB, Suharyanto, Wijayanti N, Purnobasuki H. 2019. Morpho-anatomical structure and DNA barcode of Sonchus arvensis L. Biodiversitas 20: 2417-2426. Tempuyung or show thistle (Sonchus arvensis L.) belongs to the Asteraceae. Morpho-anatomy and DNA (Deoxyribonucleic Acid) barcoding of the plant correlates with species identification and metabolite synthesis. This research aims to look at morpho-anatomical structures and analyze the DNA barcode of Sonchus arvensis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…The visualization results are not much different from the research conducted by Ilham et al (2022), in which rbcL gene in Achillea millefolium has a size of approximately 500 bp and matK has a size of 750 bp. Those studies used the same primer, which was also used by Wahyuni et al (2019).…”
Section: Dna Barcoding Pcr Amplification and Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…The visualization results are not much different from the research conducted by Ilham et al (2022), in which rbcL gene in Achillea millefolium has a size of approximately 500 bp and matK has a size of 750 bp. Those studies used the same primer, which was also used by Wahyuni et al (2019).…”
Section: Dna Barcoding Pcr Amplification and Sequencingmentioning
confidence: 99%
“…The presence of bioactive components can be found by analyzing plant extracts, especially on the leaves (Phong et al 2022). Wahyuni et al (2019) add that secondary metabolites can be found in specific areas of plant organs. To comprehend the location of cells that store the secondary metabolites, anatomical research is necessary (Ilham et al 2022), since anatomical characteristics can also help identify plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rbcL region has been used to differentiate four seagrass species from Thailand (Osathanunkul et al 2015), identify Halophila spp. from Sri Lanka (Liu et al 2020), and identify other flowering plants such as Sonchus arvensis (Wahyuni et al 2019) and genus Piper (Naim and Mahboob 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Sonchus arvensis L., an annual herb that belongs to Asteraceae, has an erect habit that reaches 64 cm in height [5]. In Indonesia, it is the 7 th most popular medicinal plant [6].…”
Section: Introductionmentioning
confidence: 99%